Refinery Wastewater Biological Treatment: A Short Review - Ishak, Syukriyah (2012)
This review presents biological treatment methods for petroleum refinery wastewater, their applications, advantages and disadvantages. It covers refinery wastewater characteristics, different categories of biological treatment systems (suspended, attached and hybrid growth) and comparison between each system with conventional activated sludge process.